Differences of Student Learning Achievement Using Cooperative Learning Models of Student Team Achievement Division (STAD) Type with Jigsaw Reviewed from the Student’s Entry Behavior - Lubis, Latifah Hanum (Budapest International Research and Critics University, 2020)
The purpose of this study was to determine differences in students’ learning achievement taught by cooperative learning type STAD and those who are taught by cooperative learning type Jigsaw, in terms of the students’ entry behaviour in grade IV students in SDN 118236 AFD 11 PAT Aek Batu Cikampak 2019 school year 2019/2020. The population of this study was all grade IV students of SDN 11836 AFD 11 PAT Aek Batu Cikampak in 2019/2020. The sample of this study was students from two classes randomly chosen. Forty students from one class was taught with the STAD type cooperative learning model and the other forty students from the other class was taught with the Jigsaw type cooperative learning model. Data was analyzed using two way Anova test (two way Anova). The results of this study indicate that the effect of the two learning model to learning achievement is significant (tcount 8,354 < ttable 3,16). The effect of the low and high score of students’ entry behavior to learning achievement is also significant (Fcount 40,820>Ftable 3,16). However, The effect of the learning model and students’ entry behavior simultaneously to learning achievement is not significant (Fcount 0,208< Ftable 3,16).